The impact of corporate social responsibility performance on earnings management: Family versus non-family firms - Borralho, J; Gallardo-Vázquez, D.; Hernández-Linares, R.; Paiva, I. (Actas del XIX Encuentro Internacional AECA, 2020)
The study analyses the impact of corporate social responsibility performance on earnings management in family firms as compared with non-family firms. We analysed 650 Spanish firms, listed and unlisted, in the period 2011-2016. The result shows a higher quality of financial information in family firms, a relationship which is reinforced by good governance factors, including the participation of women in management. The factors analysed are supported by agency and institutional theories. The study contributes to reducing the gap in the literature on the quality of financial information associated with family firms vs. non family firms.